63 Clinical & Cytological Study on Klinefelter Syndrome - Siddanagouda M Biradar; Rudragouda S Bulagouda; Gurushantappa Kadakol (Dr. Annil Mahajan, 2022)
Klinefelter Syndrome is a chromosomal disorder with addition of X sex chromosome (47XXY) in males. A patient attended to our hospital with loss of secondary sexual characteristics and male infertility. Physical examination revealed thin built, hypogonadism and absence of pubic hairs. Karyotype and biochemical analysis were performed to detect chromosomal abnormality as well as hormonal level to confirm the diagnosis of Klinefelter syndrome.